Critical Thinking as a Mediator in The Relationship Between Self-Efficacy and Innovative Behavior of Lecturers - Netty Merdiaty; Rijal Abdillah; Wustari L. Mangundjaya (Journal An-Nafs: Kajian Penelitian Psikologi, 2025)
In the context of rapid technological change and global transformation in higher education, innovative behavior among lecturers has become increasingly important. This study aims to examine the mediating role of critical thinking in the relationship between self-efficacy and innovative behavior among Indonesian university lecturers. Using a quantitative research design, data were collected from 200 active lecturers employed at higher education institutions in Bekasi and Jakarta and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The analysis involved measurement model evaluation and structural model testing to ensure construct reliability and validity. The results indicate that self-efficacy has a significant positive effect on both innovative behavior and critical thinking. Furthermore, critical thinking exerts a significant positive influence on innovative behavior and partially mediates the relationship between self-efficacy and innovative behavior. These findings highlight the importance of integrating motivational and cognitive factors to foster innovation in academic contexts. From an educational psychology perspective, this study contributes to a deeper understanding of the psychological mechanisms through which self-efficacy translates into innovative behavior, particularly through critical thinking. The findings offer theoretical contributions to social cognitive and innovation theories and provide practical implications for higher education institutions in designing professional development programs that strengthen lecturers’ self-efficacy and critical thinking skills to support sustainable innovation.